B Cell Lymphocytosis in Juvenile Dermatomyositis - Christopher Costin; Amer Khojah; Elisa Ochfeld; Gabrielle Morgan; Saravanan Subramanian; Marisa Klein-Gitelman; Xiao-Di Tan; Lauren M. Pachman (Diagnostics, 2023)
In this study, we determined if B lymphocytosis may serve as a JDM biomarker for disease activity. Children with untreated JDM were divided into two groups based on age-adjusted B cell percentage (determined through flow cytometry): 90 JDM in the normal B cell group and 45 in the high B cell group. We compared through T-testing the age, sex, ethnicity, duration of untreated disease (DUD), disease activity scores for skin (sDAS), muscle (mDAS), total (tDAS), CMAS, and neopterin between these two groups. The patients in the high B cell group had a higher tDAS (p = 0.009), mDAS (p = 0.021), and neopterin (p = 0.0365). Secondary analyses included B cell values over time and BAFF levels in matched patients with JM (juvenile myositis) and concurrent interstitial lung disease (ILD); JM alone and healthy controls Patient B cell percentage and number was significantly higher after 3–6 months of therapy and then significantly lower on completion of therapy (p =< 0.0001). The JM groups had higher BAFF levels than controls 1304 vs. 692 ng/mL (p = 0.0124). This study supports B cell lymphocytosis as a JDM disease-activity biomarker and bolsters the basis for B cell-directed therapies in JDM.